Cognitive diagnostic assessment in educational testing: a score strategy-based evaluation - Muhamad Firdaus Mohd Noh; Mohd Effendi @ Ewan Mohd Matore; Nur Ainil Sulaiman; Mohd Tarmizi Azeman; Hamzah Ishak; Nursohana Othman; Nurbaya Mohd Rosli; Siti Hannah Sabtu (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cognitive diagnostic assessment (CDA) represents an innovative approach in educational testing, utilizing cognitive diagnosis models (CDMs) to uncover specific cognitive attributes that influence students' responses to assessment items. Unlike traditional assessments, CDA offers detailed, actionable insights into individual learning processes, enabling more targeted and personalized educational interventions. However, the implementation of CDA is still underexplored compared to other psychometric theories, especially in Malaysia. Therefore, this study seeks to describe the application of CDA in Malaysia through the SCORE analysis model method. The SCORE model of CDA is evaluated across five key elements: Strengths (S), Challenges (C), Options (O), Responses (R), and Effectiveness (E) by analyzing past literature sourced from reputable databases such as Google Scholar, SCOPUS, and Web of Science. The findings indicate that CDA offers strengths like granular feedback, enhanced validity, and data-driven decisions, but faces challenges in complex implementation and resource demands. Its effectiveness hinges on efficient implementation and appropriacy, while exploring opportunities, managing risks, and considering stakeholders' responses help optimize its transformational and commercial value. The findings provide educators with a framework for utilizing CDA to enhance instructional strategies and tailor interventions to meet individual student needs. For policymakers, the implications of the strengths, challenges, and opportunities of CDA emphasize the importance of supporting its implementation through professional development, infrastructure investment, and policy alignment. Future studies are recommended to explore the long-term impacts of CDA on student achievement and educational equity, scalability across educational levels, and development of user-friendly tools to enhance accessibility for educators.